Conversion surgery for stage IV gastric cancer: a multicenter retrospective study - Kano, Yosuke; Ichikawa, Hiroshi; Hanyu, Takaaki; Muneoka, Yusuke; Ishikawa, Takashi; Aizawa, Masaki; Matsuki, Atsushi; Yabusaki, Hiroshi; Bamba, Takeo; Nakagawa, Satoru; Kobayashi, Kazuaki; Kuwabara, Shirou; et al. (BMC surgery, 2022)
Background Recent improvements in systemic chemotherapy have provided an opportunity for patients with stage IV gastric cancer (GC) to undergo conversion surgery (CS). The aim of this study was to evaluate the long-term outcomes of patients who underwent CS and to elucidate the prognostic factors for CS in stage IV GC. Methods A total of 79 patients who underwent CS with the aim of R0 resection for stage IV GC at six institutions from January 2008 to July 2019 were enrolled. We retrospectively reviewed the clinicopathological data and prognosis. Results Of the 79 patients, 23 (31.1%) had initially resectable disease (IR) before chemotherapy, defined as positive for cancer on peritoneal cytology (CY1), resectable hepatic metastasis, or para-aortic lymph node No. 16a2/b1 metastasis. Of the 56 remaining patients with primary unresectable disease, 39 had peritoneal dissemination. R0 resection was accomplished in 63 patients (79.7%). The 3-year OS rates for patients with IR and unresectable disease were 78.3% and 44.5%, respectively. Multivariate analysis showed that IR ( P = 0.014) and R0 ( P = 0.014) were statistically significant independent prognostic factors for favorable OS. Among patients with peritoneal dissemination alone, OS was significantly better for patients with R0 resection than for patients with R1/2 resection, with the 3-year OS rates of 65.5% and 23.1%, respectively ( P = 0.011). Conclusions CS is a treatment option for selected patients with stage IV GC. Patients with IR and patients who achieve R0 resection may obtain a survival benefit from CS.